Sistem Keuangan Pengelola Anggaran Berbasis Web di SMK Tunas Pemuda - Rahmat Ibnu Iman; Silvi Maerosa; Siti Ayu Nurfadillah; Wasis Haryono (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
A web-based budget management information system is a modern solution for efficient school financial administration. This system facilitates the process of budget recording, monitoring, and reporting, leading to faster, more precise, and accurate work. SMK Tunas Pemuda, as a vocational high school, currently manages its budget manually, which is prone to recording errors, data loss, or damage. These issues include managing income from various sources, allocating expenditures, and generating accurate financial reports. Given these challenges The study focuses on designing and implementing a digital platform for managing school budgets. budget management financial system application at SMK Tunas Pemuda. This application is designed to simplify the budget management process, from recording every income and expenditure transaction, monitoring fund allocation, to printing budget reports and transaction proofs. The Waterfall development method is used to develop this application systematically and structured through planning, analysis, design, implementation, and testing phases. Based on the test results, the system has been successfully created and proven 100% compliant with user expectations, simplifying the budget management process, and increasing effectiveness and efficiency. This application also allows for printing budget reports and transaction proofs for both income and expenditure.